Dose- and Time-Dependent Cytotoxicity of Carteolol in Corneal Endothelial Cells and the Underlying Mechanisms - Su, Wen; Zhao, Jun; Fan, Ting-Jun (Frontiers in Pharmacology, 2020)
Carteolol is a nonselective β-adrenoceptor antagonist used for the treatment of glaucoma, and its abuse might be cytotoxic to the cornea. However, its cytotoxicity and underlying mechanisms need to be elucidated. Herein, we used an in vivo model of feline corneas and an in vitro model of human corneal endothelial cells (HCECs), respectively. In vivo results displayed that 2% carteolol (clinical dosage) could induce monolayer density decline and breaking away of feline corneal endothelial cells. An in vitro model of HCECs that were treated dose-dependently (0.015625-2%) with carteolol for 2-28 hours, resulted in morphological abnormalities, declining in cell viability and elevating plasma membrane permeability in a dose- and time- dependent manner. High-dose (0.5%-2%) carteolol treatment induced necrotic characteristics with uneven distribution of chromatin, marginalization and dispersed DNA degradation, inactivated caspase-2/-8, and increased RIPK1, RIPK3, MLKL and pMLKL expression. The results suggested that high-dose carteolol could induce necroptosis via the RIPK/MLKL pathway. While low-dose (0.015625%-0.25%) carteolol induced apoptotic characteristics with chromatin condensation, typical intranucleosomal DNA laddering patterns, G1 cell-cycle arrest, phosphatidylserine externalization and apoptotic body formation in HCECs. Meanwhile, 0.25% carteolol treatment resulted in activated caspase-2, -3, -8 and -9, down-regulation of Bcl-2 and Bcl-xL, up-regulation of Bax and Bad, ΔΨm disruption and release of cytoplasmic cytochrome c and AIF into the cytoplasm. These observations suggested that low-dose carteolol could induce apoptosis via a caspase activated and mitochondrial-dependent pathway. These results suggested that carteolol should be used carefully, as low as 0.015625% cartelol caused apoptotic cell death in HCECs in vitro.